Search for charged-lepton flavor violation in top quark production and decay in pp collisions at √s = 13 TeV - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Journal of high energy physics)
Results are presented from a search for charged-lepton flavor violating (CLFV) interactions in top quark production and decay in pp collisions at a center-of-mass energy of 13 TeV. The events are required to contain one oppositely charged electron-muon pair in the final state, along with at least one jet identified as originating from a bottom quark. The data correspond to an integrated luminosity of 138 fb(-1), collected by the CMS experiment at the LHC. This analysis includes both the production (q -> e mu t) and decay (t -> e mu q) modes of the top quark through CLFV interactions, with q referring to a u or c quark. These interactions are parametrized using an effective field theory approach. With no significant excess over the standard model expectation, the results are interpreted in terms of vector-, scalar-, and tensor-like CLFV four-fermion effective interactions. Finally, observed exclusion limits are set at 95% confidence levels on the respective branching fractions of a top quark to an e mu pair and an up (charm) quark of 0.13 x 10(-6) (1.31 x 10(-6)), 0.07 x 10(-6) (0.89 x 10(-6)), and 0.25 x 10(-6) (2.59 x 10(-6)) for vector, scalar, and tensor CLFV interactions, respectively.